Fundamentals of Hysteresis in Perovskite Solar Cells: From Structure‐Property Relationship to Neoteric Breakthroughs. Issue 1 (21st August 2021) - Wali, Qamar; Aamir, Muhammad; Ullah, Abid; Iftikhar, Faiza Jan; Khan, Muhammad Ejaz; Akhtar, Javeed; Yang, Shengyuan
Abstract: Perovskite solar cells (PSC) have shown a rapid increase in efficiency than other photovoltaic technology. Despite its success in terms of efficiency, this technology is inundated with numerous challenges hindering the progress towards commercial viability. The crucial one is the anomalous hysteresis observed in the photocurrent density‐voltage (J−V) response in PSC. The hysteresis phenomenon in the solar cell presents a challenge for determining the accurate power conversion efficiency of the device. A detailed investigation of the fundamental origin of hysteresis behavior in the device and its associated mechanisms is highly crucial. Though numerous theories have been proposed to explain the causes of hysteresis, its origin includes slow transient capacitive current, trapping, and de‐trapping process, ion migrations, and ferroelectric polarization. The remaining issues and future research required toward the understanding of hysteresis in PSC device is also discussed. Abstract : Metal halide perovskite solar cells have gained enormous attention with remarkable power conversion efficiency in a short during of time compared to other photovoltaic systems. However, hysteresis in the metal halide perovskite solar cells is one of the major challenges that need to be addressed. This review will help to understand the fundamentals of hysteresis with respect to structure property‐relationship and breakthroughs to tackle hysteresis in metal halide perovskite solar cells.